It keeps on turning: effects of prolonged long-term left ventricular assist device support as a bridge to heart transplantation - Schmack, Bastian; Grossekettler, Leonie; Ruhparwar, Arjang; Zeriouh, Mohamed; Weymann, Alexander; Mohite, Prashant; Koch, Achim; Simon, Andre Rüdiger; Sabashnikov, Anton; Popov, Aron Fredrik (The international journal of artificial organs, 2019)
Objectives:Increasing incidence of end-stage heart failure has moved the therapy with left ventricular assist devices to the forefront of surgical treatment. Moreover, continuous sophistication in this technology has resulted in increasing proportion of patients on prolonged support. Early and late complications after left ventricular assist device as a bridge to transplantation and present factors associated with long-term support and long-term outcomes of patients supported for at least 1?year were compared.Methods:A total of 163 consecutive patients who underwent left ventricular assist device implantation as bridge to transplantation were included. A total of 79 patients were supported for at least 1?year (long-term support), whereas 84 patients were supported for less than 1?year (short-term group).Results:Factors associated with a successful long-term support were male gender (p?
Article first published online: December 24, 2018
Gesehen am 03.04.2019